2009
DOI: 10.1002/ab.20295
|View full text |Cite
|
Sign up to set email alerts
|

Desensitization to media violence over a short period of time

Abstract: This study investigated the desensitization to violence over a short period of time. Participants watched nine violent movie scenes and nine comedy scenes, and reported whether they enjoyed the violent or comedy scenes and whether they felt sympathetic toward the victim of violence. Using latent growth modeling, analyses were carried out to investigate how participants responded to the different scenes across time. The findings of this study suggested that repeated exposure to media violence reduces the psycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(71 citation statements)
references
References 35 publications
4
65
1
1
Order By: Relevance
“…This notion is in line with modern extensions of the GAM, which suggest that desensitization specifically leads to a reduction of sympathy for the victim (Bushman & Anderson, 2009;Carnagey et al, 2007). It is also supported by findings from an experimental study demonstrating a reduction of sympathy (e.g., "At the end of the clip I felt sorry for the victim of violence") after repeated exposure to violent clips (Fanti, Vanman, Henrich, & Avraamides, 2009). Based on the measurement issues associated with prior work, as well as theoretical accounts, we posit the following hypothesis:…”
Section: Equating Empathy and Sympathysupporting
confidence: 81%
“…This notion is in line with modern extensions of the GAM, which suggest that desensitization specifically leads to a reduction of sympathy for the victim (Bushman & Anderson, 2009;Carnagey et al, 2007). It is also supported by findings from an experimental study demonstrating a reduction of sympathy (e.g., "At the end of the clip I felt sorry for the victim of violence") after repeated exposure to violent clips (Fanti, Vanman, Henrich, & Avraamides, 2009). Based on the measurement issues associated with prior work, as well as theoretical accounts, we posit the following hypothesis:…”
Section: Equating Empathy and Sympathysupporting
confidence: 81%
“…One study that compared repeated exposure to arousing comedic versus violent film clips found a much weaker and different pattern of desensitization in response to comedic clips, suggesting that arousal is not sufficient to produce desensitization. 13 Other research reached the same conclusion. 18 Parents were asked, "How likely is it that you would allow (target child) to see this movie in the future?"…”
Section: Figuresupporting
confidence: 53%
“…1 An alternative and not necessarily incompatible explanation for this "ratings creep" is that parents on CARA' s rating board and in the general population have become desensitized by repeated exposure to increasing amounts of violence and sex in films. 5 Desensitization occurs when repeated exposure to a disturbing stimulus reduces the emotional response to that content, 7 a phenomenon that has been observed in response to violent [8][9][10][11][12][13] and sexual media. 14 Consistent with this interpretation, a Kaiser Family Foundation survey of over 1000 parents found that parents were less concerned about their children' s exposure to sex (51% vs 67%) and violence (46% vs 62%) in 2006 than in 1998.…”
Section: Discussionmentioning
confidence: 99%
“…This theory is supported by research showing that violent media exposure is associated with decreased cardiovascular (e.g., Carnagey, Anderson, & Bushman, 2007;Linz, Donnerstein, & Adams, 1989), electrodermal (e.g., Cline, Croft, & Courier, 1973), neural (Bartholow, Bushman, & Sestir, 2006), and empathic responses (e.g., Fanti, Vanman, Henrich, & Avraamides, 2009) during depictions of real violence.…”
mentioning
confidence: 86%